Impact of Telecommunication Infrastructure, Market Size, Trade Openness and Labor Force on Foreign Direct Investment in ASEAN - Meidayati, Anis Wahyu (Universitas Airlangga, 2017)
Foreign Direct Investment (FDI) in recent years has created a positive impact for ASEAN countries. FDI give spillover effects that directly contribute capital improvements, technological developments, and global market access, also skills and managerial transfers. In order to attract FDI inflow into country, ASEAN member countries need to know what factors which attract investment related to the needs of infrastructure types and other factors. The purpose of this study is examining the determinant of FDI in ASEAN countries. This research method used is panel data regression period 2005-2015 from 10 countries in ASEAN. The results showed simultaneously and partially telecommunication infrastructure, market size, trade openness, and labor force variable have significant relationship with FDI inflows in ASEAN countries. Keywords: Telecommunication Infrastructure, Market Size, Trade Openness, Labor Force, FDIJEL: L96, L11, B17, J21, F21